Computational Methods for Study of Hydrogen Bonding Between Phenol Derivatives with Ethanol - Rezaei Sameti, Mahdi (Asian Journal of Chemistry, 2010)
It is common practice in computational chemistry to model the behaviour of bulky compounds from simplified structures. This procedure enables the use of higher computational levels, with generally improved results. The most crucial problem in this methodology is choosing how simple the structures in question should be. In fact, oversimplification in this context can lead to a highly different behavior relative to starting one. In order to check how valid this approach is, in this work the author modelled intermolecular hydrogen bonding between phenol derivatives with ethanol. The calculations were carried out with the Gaussian 98 suite of programs. The geometry of all structures involved in gas phase is fully optimized at HF at the 6-31G** level. The result shows that strength of hydrogen bonding and the dipole moment in meta position is larger than other positions in all system.